Orthomosaic Image and Digital Surface Model for the Bugeye Lakes Complex, Arctic Coastal Plain of northern Alaska, July 2022 ... - Jones, Benjamin; Ward Jones, Melissa (NSF Arctic Data Center, 2023)
Taken together, lakes and drained lake basins may cover up to 80% of the lowland landscapes in permafrost regions of the Arctic. Lake formation, growth, and drainage in lowland permafrost regions create a terrestrial and aquatic landscape mosaic of importance to geomorphic and hydrologic processes, tundra vegetation communities, permafrost and ground-ice characteristics, biogeochemical cycling, wildlife habitat, and human land-use activities. Our project focuses on quantifying the role of thermokarst lake expansion, drainage, and drained lake basin evolution in the Arctic System. We did this through a combination of field studies, environmental sensor networks, remote sensing, and modeling. This dataset consists of an orthomosaic and digital surface model (DSM) derived from drone surveys on 19 and 20 July 2022 at the Bugeye Lakes Complex on the Arctic Coastal Plain of northern Alaska. 5,968 digital images were acquired from a DJI Phantom 4 Real-Time Kinematic (DJI P4RTK) quadcopter with a DJI D-RTK 2 Mobile ...